SEMANTIC AND AXIOLOGY OF 7 YEARS SONG AS ENGLISH MATERIAL CHOICE FOR YOUNG LEARNERS - 'Ain, Qurrata; Triyono, Sulis (LLT Journal: A Journal on Language and Language Teaching, 2019)
The implication of curriculum 2013, the song is one of the topics to achieve the goal of learning. Learning through song emphasizes that the teacher should know the best song choice based on the axiology and semantic meaning. Not all the song can be as material for students. The teacher should evaluate based on level of the students. a song, there were a meaning that would be expressed and moral values so that it will be interested to find out what the song?s lyric want to deliver. Some people often sing a song without know the explicit and implicit meaning of the lyric. There was also an existence of value. This research focuses (1) to analyze the lexical and contextual meaning in song lyric and (2) to know the implication of values that found in ?7 years? lyric by Lukas Graham (2) to evaluate 7 years whether or not to be as teaching material. This research used descriptive qualitative method. The object of the research was 7 years by Lukas Graham. The researcher found lyric and analyze the lexical and contextual meaning. Then, it was related with the implication of axiology in semantic analysis of song?s lyric ?7 years? by Lukas Graham. The finding of semantic analysis, there are 35 for lexical meaning and 14 for contextual meaning. Then, for the lexical meaning is so different with contextual meaning. By knowing lexical and contextual meaning, it would make the listener understand and the meaning which delivered of song lyric by Lukas Graham.  There is an implication of axiology in semantic analysis of lyric ?7 years?. This song contains esthetic and ethic based on the axiology theory. The axiology contained in song lyric can be material for students. It tells about the story of writer starting the writer was born till his father died. All of the life experiences contain in song lyric. DOI: 10.24071/llt.2019.220210